2022
DOI: 10.3389/fnmol.2022.984776
|View full text |Cite
|
Sign up to set email alerts
|

IQSEC2-related encephalopathy in male children: Novel mutations and phenotypes

Abstract: The isoleucine–glutamine (IQ) motif and Sec7 domain-containing protein 2 (IQSEC2) gene, located at Xp11. 2, are associated with nervous system diseases, such as epilepsy, autism, and intellectual disabilities. Gender-related differences in the severity of phenotype severity have been described previously. Here, we report the details of seven male children with IQSEC2 mutations from different families. During this investigation, we explored the relationship between the genotype and phenotype of IQSEC2 mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Brain magnetic resonance imaging (MRI) revealed small, broad, and flat gyri in the bilateral multiple lobes, indicating pachygyria ( Figures 1C – F ). Genomic DNA of the proband and her parents was extracted from peripheral blood for trio-whole-exome-sequencing (WES), using a method similar to that used in our previous study ( 15 ).The results revealed a de novo heterozygous variant (p.Arg292Trp) in the DYNC1H1 gene. In silico analysis using PolyPhen-2 and MutationTaster further indicated that the p.Arg292Trp mutation was “probably damaging,” which was consistent with the PROVEAN server data; the variant was categorized as probably pathogenic according to the American College of Medical Genetics and Genomics guidelines ( Supplementary Figure S1 ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Brain magnetic resonance imaging (MRI) revealed small, broad, and flat gyri in the bilateral multiple lobes, indicating pachygyria ( Figures 1C – F ). Genomic DNA of the proband and her parents was extracted from peripheral blood for trio-whole-exome-sequencing (WES), using a method similar to that used in our previous study ( 15 ).The results revealed a de novo heterozygous variant (p.Arg292Trp) in the DYNC1H1 gene. In silico analysis using PolyPhen-2 and MutationTaster further indicated that the p.Arg292Trp mutation was “probably damaging,” which was consistent with the PROVEAN server data; the variant was categorized as probably pathogenic according to the American College of Medical Genetics and Genomics guidelines ( Supplementary Figure S1 ).…”
Section: Case Presentationmentioning
confidence: 99%